Chemical composition of four cultivated tropical bamboo in genus gigantochloa - Razak Wahab; Mohd Tamizi Mustafa; Mohammed Abdus Salam; Mahmud Sudin; Hashim W. Samsi; Mohd Sukhairi Mat Rasat (Canadian Center of Science and Education, 2013)
The chemical compositions of cultivated 3 year-old bamboo culms of Gigantochloa brang, G. levis, G. scortechinii and G. wrayi were studied. The culms exhibited different chemical composition in extractives, α-cellulose, lignin and ash contents between the bamboo species, location in the culms and position at the nodes and internodes. The extractive content in four species ranged from 8.30 to 9.23%. The extractive content of G.brang, G.levis, G.scortechinii and G.wrayi were 8.30%, 9:23%, 8:00% and 8.62% respectively. The holocellulose content for G. levis were 85.08%, G. wrayi 84.53%, G. brang 79.94% and G. scortechinii 74.62%. The holocellulose content for the cultivated bamboo genus Gigantochloa were 74% to 85%. The α- cellulose is the chemical constituents in the holocellulose. The highest was G.brang (51.58%) followed by G. scortechinii (46.87%), G. wrayi (37.66%) and G. levis (33.80%). The lignin content ranged between 24.84 to 32.65%. The highest were obtained in G. scortechinii (32.55%), G. wrayi (30.04%), G. levis (26.50%) and lowest in G. brang (24.83%). The ash content in four species of Gigantochloa bamboo ranged between 0.88 to 2.86%. The ash content is the highest in G. scortechinii (2.83%) follow by G. levis (1.29%), G. brang (1.25%) and the lowest in G. wrayi (0.88%).